The Mechanism of Damage to the Midgut by Low Concentration of Bacillus thuringiensis in the Silkworm, Bombyx mori - Hongbin Zou; Haoyi Gu; Jialu Cheng; Chao Tian; Qilong Shu; Peilin Peng; Bing Li (Insects, 2024)
Bacillus thuringiensis (Bt) has been extensively applied in agricultural pest management, posing a notable ecological risk to beneficial insects like Bombyx mori (silkworms). However, the toxicological mechanisms of Bt at low concentrations on silkworms remain largely unexplored. In this study, we determined the LC50 (96 h) of Bt for fifth-instar silkworm larvae to be 0.08 × 10−3 mg/L. Exposure to a sub-lethal concentration of Bt (1/2 LC50) led to significant reductions in body weight, pupal size, and the weights of both the whole cocoon and cocoon shell. Histopathological and ultrastructural examinations revealed that Bt exposure caused severe damage to the microvilli and epidermal cells of the midgut. Transcriptome sequencing of the midgut identified 290 differentially expressed genes (DEGs), with these genes predominantly involved in metabolic processes and apoptotic pathways. Notably, apoptosis-related genes such as Apaf-1 and Caspase-3 were upregulated by 5.08-fold and 1.27-fold, respectively. Further validation through TUNEL assays and Western blotting analysis confirmed a significant activation of apoptotic signaling. These findings suggested that low concentrations of Bt could trigger apoptotic pathways in the midgut of silkworm larvae, providing valuable insights into the toxicological evaluation of Bt at sub-lethal doses in insect species.